Pontos críticos no controle de insetos em equipamentos e estruturas de armazenagem de grãos - Kessler, Moacir (2006)
This work had as objective to identify the critical points of insect control in structures of grain storage. The study was realized in the period of reception of the soy and maize harvest of 2006 in seven typical storing units of Western Paran? State. The presented data had been object of inspecting in the respective storing units during the reception of the harvest and aimed to identify the points inspected in the units; the presence of adult insects, the accumulation of residues, the difficulty of access to the place for cleanness, the lack of planning of the structure for the cleanness of the place and the lack of planning or of the project of the equipment aiming at its cleanness. The study proves that the inappropriateness of the installations and of the equipment is the cause of focus of infestation for insects, compromising the quality of the stored product beyond generating incidental costs to the storekeeper. The work objectified not only to present the critical points of insect control plague in the storage structures; as mainly to consider techniques of cleanness of the installations, of the equipment, to consider adjustments in the equipment and the installations being aimed at improvement in the cleanness and reduction or elimination of the deposited residues and consequent elimination of the focus of infestation, still considers changes in the projects of new storing units and equipment so that the same ones have a new concept in the conception of the projects and construction aiming the non deposition of residues, critical points of development of insects.